CEO ownership, external governance, and risk-taking - Kim, E. Han; Lu, Yao (Journal of Financial Economics, 2011)
This paper shows the relation between CEO ownership and firm valuation hinges critically on the strength of external governance (EG). The relation is hump-shaped when EG is weak, but is insignificant when EG is strong. The results imply that CEO ownership and EG are substitutes for mitigating agency problems when ownership is low. However, very high levels of share ownership can reduce firm value by entrenching the CEO and discouraging him from taking risk, unless mitigated by strong EG. We identify channels through which CEO ownership affects firm value by examining R&D, which is discretionary and risky. We find CEO ownership similarly exhibits a hump-shaped relation with R&D when EG is weak, but no relation when EG is strong. Our results are robust to endogeneity issues concerning CEO ownership and EG.